1999
DOI: 10.1021/tx980001t
|View full text |Cite
|
Sign up to set email alerts
|

Procainamide, a Drug Causing Lupus, Induces Prostaglandin H Synthase-2 and Formation of T Cell-Sensitizing Drug Metabolites in Mouse Macrophages

Abstract: Procainamide (PA) may cause drug-induced lupus, and its reactive metabolites, hydroxylamine-PA (HAPA) and nitroso-PA, are held responsible for this. Here, we show that N-oxidation of PA to these metabolites can take place in macrophages and lead to formation of neoantigens that sensitize T cells. Murine peritoneal macrophages (PMvarphi), exposed to PA in vitro, generated neoantigens related to HAPA as indicated by (1) their capacity to elicit a specific recall response of HAPA-primed T cells in the adoptive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…In the first of these two companion articles, we demonstrate that cytochromes P450 do not play a major role in the protein haptenation observed in NHEKs exposed to SMX or DDS. In addition, although other investigators have reported that cyclooxygenase-2 is able to oxidize arylamine compounds (Goebel et al, 1999), our results indicate that neither cyclooxygenase-1 nor -2 is involved in the protein haptenation observed in these cells (Vyas et al, 2006). Hence, we probed the role of flavin-containing monooxygenases (FMOs) and peroxidases (PRXs) in this phenomenon.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In the first of these two companion articles, we demonstrate that cytochromes P450 do not play a major role in the protein haptenation observed in NHEKs exposed to SMX or DDS. In addition, although other investigators have reported that cyclooxygenase-2 is able to oxidize arylamine compounds (Goebel et al, 1999), our results indicate that neither cyclooxygenase-1 nor -2 is involved in the protein haptenation observed in these cells (Vyas et al, 2006). Hence, we probed the role of flavin-containing monooxygenases (FMOs) and peroxidases (PRXs) in this phenomenon.…”
mentioning
confidence: 68%
“…Oxidation of SMX and DDS to their arylhydroxylamine and then subsequently to arylnitroso metabolites is believed to be a critical step in their ability to cause CDRs (Naisbitt et al, 1999;Svensson et al, 2001). Various hepatic enzymes, such as the cytochrome P450-dependent monooxygenases, cyclooxygenases, and PRXs, have been shown to be active in SMX and DDS metabolism (Cribb et al, 1990;Mitra et al, 1995;Goebel et al, 1999;Winter et al, 2000). Although survival of reactive metabolites during transit from liver to skin has not been demonstrated, evidence suggests the presence of the hydroxylamine metabolites of these drugs in plasma and urine after therapeutic doses (Coleman et al, 1992;Mitra et al, 1995;Winter et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Bioactivation of these drugs to their reactive metabolites followed by binding to intracellular proteins has been suspected to play a key role in eliciting the immune response. In addition to liver microsomes, formation of these drug-protein covalent adducts have already been demonstrated in various nonhepatic cellular models, including keratinocytes , fibroblasts (Bhaiya et al, 2006), monocytes (Goebel et al, 1999), and a T cell line (Manchanda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several arylamine drugs, including procainamide, are oxidized to arylhydroxylamine metabolites by COX-2 in vitro (Liu and Levy, 1998;Goebel et al, 1999). Which of these enzymes, if any, mediates the bioactivation of SMX and DDS in NHEKs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxylation of SMX and DDS by various CYP450s has been reported (Cribb et al, 1995;Mitra et al, 1995;Gill et al, 1999;Winter et al, 2000). Several arylamine drugs, including procainamide, are oxidized to arylhydroxylamine metabolites by COX-2 (Liu and Levy, 1998;Goebel et al, 1999).…”
mentioning
confidence: 99%